Physical Education in Chile: towards a transdisciplinarity from the curriculum and the pedagogical collaboration (Praxis Educativa, 2020)
Chilean educational system includes Physical Education as the school discipline responsible for motor competence, reduced to a technical and mechanistic dimension for the body and movement. Although it appears as a possibility to the formation of an integral human being, the fragmented curriculum limits a holistic, meaningful and experiential education that the motor experience can provide. An education thatgoes beyond disciplines is transcendental and necessary for the human potentialities development in their multiplicity from the authentic possibilities that the Human Motricity manifestations can offer. The intentionally, reflective and collaborative curricular and didactic projects make possible classroom practices that go across the disciplines to a genuine interaction of a motor and bodily being into its closest reality, and that complex, meaningful and experiential reality must transcend the prescribed school and curricular structure.
Keywords: Physical Education; teaching profession; interdisciplinary approach; curriculum development; basic skills